Analysis of a rice blast resistance gene Pita-Fuhui2663 and development of selection marker - Niqing He; Fenghuang Huang; Mingxiang Yu; Yebao Zhu; Qingshun Q. Li; Dewei Yang (Scientific Reports, 2022)
Abstract Rice blast is a detrimental rice disease caused by the fungus Magnaporthe oryzae. Here, we identified a resistance gene from the rice cultivar Fuhui 2663 which is resistant to the rice blast isolate KJ201. Through isolated population analyses and sequencing approaches, the candidate gene was traced to chromosome 12. With the use of a map-based cloning strategy, the resistance gene was ultimately mapped to an 80-kb resistance locus region containing the Pita gene. Candidate gene prediction and cDNA sequencing indicated that the target resistance gene in Fuhui 2663 was allelic to Pita, thus being referred to as Pita-Fuhui2663 hereafter. Further analysis showed that the Fuhui 2663 protein had one amino acid change: Ala (A) residue 918 in Pita-Fuhui2663 was replaced by Ser (S) in Pita-S, leading to a significant change in the 3D structure of the Pita-S protein. CRISPR/Cas9 knockout experiments confirmed that Pita-Fuhui2663 is responsible for the resistance phenotype of Fuhui 2663. Importantly, Pita-Fuhui2663 did not affect the main agronomic traits of the variety compared to the Pita gene as verified by knockout experiments, indicative of potential applications of Pita-Fuhui2663 in broader breeding programs. Furthermore, a Pita-Fuhui2663-dCAPS molecular marker with good specificity and high efficiency was developed to facilitate rice breeding for resistance to this devastating disease.